STRUKTUR DAN KOMPOSISI JENIS TUMBUHAN HERBA DAN SEMAI PADA HABITAT SATWA HERBIVOR DISUAKA MARGA S ATWA CIKEPUH,SUKABUMI, JAWABARAT - Asep Sadili (Research Center for Biology-Indonesian Institute of Sciences, 2010)
The research was conducted to study the structure and composition of herbaceous and seedling communities (understorey species)occurred on herbivore habitat within Cikepuh wildlife sanctuary. A series of 25 plots of 1 m x 1 m each with an interval of 5 m were used to establish a species-area relationship. The proportion (percentage) of canopy (leaf) coverage of each species occurred within the sampling plots to the sampled soil surface area was measured. A total of 54 species belonging to 47 genera and 29 families occurred in the 25 plots develoved, with the species diversity index (value) of 2.09 using the Shannon Wiener formula. Nine species were categorized as herbaceous plants (16.67 %) while the other 45 species were categorized as seedlings (83.33 %). The average density measured was 39 individuals/m or c. 386.400 individuals/ha. The most dominant family is Euphorbiaceae (possessing 5 diffrent species) while the most dominant species is Urochloa subquadripara (Poaceae) with and importance value of 96.08%.